2021
DOI: 10.1155/2021/1141619
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor Region Location and Classification Based on Fuzzy Logic and Region Merging Image Segmentation Algorithm

Abstract: Early diagnosis of tumor plays an important role in the improvement of treatment and survival rate of patients. However, breast tumors are difficult to be diagnosed by invasive examination, so medical imaging has become the most intuitive auxiliary method for breast tumor diagnosis. Although there is no universal perfect method for image segmentation so far, the consensus on the general law of image segmentation has produced considerable research results and methods. In this context, this paper focuses on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…According to the simulation environment and the Lambert model formula [ 6 ], the transmitted power of each light source is set to P ti , the received power corresponding to each light source at PD is P ri , and the distance from the light source to the PD is projected on the surface to be measured d i when the PD is placed horizontally: cos φ =cos ϕ . The noise distribution is Gaussian white noise n i , which can be obtained.…”
Section: Introduction Of Characteristic Positioning Methodsmentioning
confidence: 99%
“…According to the simulation environment and the Lambert model formula [ 6 ], the transmitted power of each light source is set to P ti , the received power corresponding to each light source at PD is P ri , and the distance from the light source to the PD is projected on the surface to be measured d i when the PD is placed horizontally: cos φ =cos ϕ . The noise distribution is Gaussian white noise n i , which can be obtained.…”
Section: Introduction Of Characteristic Positioning Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%